The Six Periods of the Creation Universe in the Perspective of the Study Quranic Interpretation with Science - Alifia Dityasari; Ika Kartika (Proceeding International Conference on Religion, Science and Education, 2023)
The universe as a creature of God with a vast expanse of reality which is full of various mysteries and secrets that will never be finished being revealed by mankind. The process of the creation of the universe as it is is constantly being investigated by scientists, and the divine existence of the tendencies from which they originated has always been a never-ending question. The Al-Quran as a miracle of God's word and complement of previous books stores information on various things. Among them are verses about science that show the majesty and power of God in this universe. On QS. An-Naziat verses 27-33 there explain the kauniyah verses of natural phenomena concerning the creation of the universe. This research uses literature research with thematic interpretation method. Through the study of interpretations by scholars with various styles, the result is that in QS. An-Naziat verses 27-33 describes how the six periods of creation regarding the universe.